Construction site safety: legal issues of liability for various parties - Shim, Mong Heng (2006)
The construction sector is an important part of the economy in most countries, yet is generally considered to be dangerous, dirty, hard and unreliable. In spite of the low attention often given to construction sites injuries in many countries, the statistics continue to be alarming. Construction workers are two to three times more likely to die on the job than workers in other industries while the risk of serious injury is almost three times higher. The construction professionals and the workers concerned with the construction process have both professional and legal duties to take care, not only of their own health and safety at work, but the health and safety of others who might be put at risk by their acts and omissions. This research aims to determine the legal position of parties in construction contract with respect to their liabilities for safety of construction worker during construction. This study will answer most of the uncertain issues that are arisen on the legal liabilities for the construction site safety of the workers. Various party involve in construction such as contractors, employers, designers, and workers himself would eager to know their liability according to construction site safety of the workers. Murdoch and Hughes (1998) had separated the parties into five groups; builders, designers, regulators, purchasers and users of buildings. Each stage in the life of a building or civil engineering structure presents hazards, some of which are common to all work in construction or unique to the particular type of project. All civil engineers and other construction professionals concerned with the construction process have both professional and legal duties to take care, not only of their own health and safety at work, but the health and safety of others who might be put at risk by their acts or omissions. Basically from the research, the construction parties will be liable for master and servant relationship, negligence, contributory negligence, occupier liability, vicarious liability and supervision liabiliti